2018
DOI: 10.1089/jpm.2018.0027
|View full text |Cite
|
Sign up to set email alerts
|

Gratitude at the End of Life: A Promising Lead for Palliative Care

Abstract: Gratitude may act positively on QoL and may protect against psychological distress in the palliative situation. The next step will be the adaptation and implementation of a gratitude-based intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 57 publications
(45 reference statements)
1
27
0
Order By: Relevance
“…One highlights positive links between growth and end of life dreams and visions (Levy et al, 2020). The other, conducted by our research team, found positive associations between gratitude and growth (Althaus et al, 2018). However, key questions of PTG prevalence and associations with psychological distress and quality of life in palliative patients remain unanswered.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…One highlights positive links between growth and end of life dreams and visions (Levy et al, 2020). The other, conducted by our research team, found positive associations between gratitude and growth (Althaus et al, 2018). However, key questions of PTG prevalence and associations with psychological distress and quality of life in palliative patients remain unanswered.…”
Section: Introductionmentioning
confidence: 80%
“…This cross-sectional study deployed standardized, validated questionnaires to collect quantitative data about palliative care patients, as part of a wider research project examining gratitude at the end of life (Althaus et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Articles included in this meta-narrative often focus on gratitude benefits as a factor that could be used instrumentally to inform care interactions. Althaus et al (2018) conclude that gratitude may have a positive impact on quality of life and reduce psychological distress in patients receiving palliative care in Switzerland. A thematic analysis of interviews with patients in a city in the United States who had suffered a traumatic spinal cord injury found that patients benefited from appraising adverse life experiences as positive through the lens of gratitude (Chun & Lee, 2013).…”
Section: Meta-narrative 4: Benefits Of Gratitudementioning
confidence: 85%
“…In this way, perhaps the process of truly receiving gratitude can be conceptualized as a form of self-care. Gratitude may be a promising focus for interventions in health care due to its positive effect on the giver ( Althaus et al, 2018 ) and receiver.…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, there is evidence that giving thanks or “practicing gratitude” can be beneficial for patients with advanced disease, resulting in an improved sense of quality of life and protection against psychosocial distress ( Althaus et al, 2018 ). Some studies also suggest that practicing gratitude helps to reduce burnout ( Chan, 2011 ; Lanham et al, 2012 ), and stress ( Krause, 2006 ; Tsui Pui, 2009 ; Wood et al, 2008 ), improves mood, self-esteem and sense of happiness ( Borgueta, 2012 ; Lee, 2017 ).…”
mentioning
confidence: 99%